Stiffness in running: A narrative integrative review - Jaén-Carrillo, D.; Roche-Seruendo, L. E.; Felton, L.; Cartón-Llorente, A.; García-Pinillos, F. (Strength and Conditioning Journal, 2021)
Researching running spatiotemporal parameters has deepened knowledge of the spring-mass model and its capacity to estimate and predict kinetic and kinematic variables. However, although the impact of lower-limb stiffness on athletic performance seems considerable, recognition of lower-limb stiffness among coaches and practitioners remains sparse. This review highlights factors influencing lower-limb stiffness during running and their relationship to injury prevention and performance. Current knowledge of lower-body stiffness during running is integrated and new scientific scope offered. Because the different variables are correlational, it is strongly recommended not to measure their effects on lower-limb stiffness individually. The spring-mass model behavior when altering variables such as footwear or foot-strike pattern needs cautious examination. Although both stretch-shortening cycle and lower-limb stiffness are key parameters in elastic strain energy storage and release during sport activities, hormonal fluctuations (particularly associated with the menstrual cycle) should draw special attention because they affect musculotendinous stiffness properties and therefore may influence athletic performance and injury prevalence. Introducing lower-limb strength training would improve the characteristics of stiffness in running, contributing to maximized performance and reduced injury risk.